ТОПЫРАҚТЫҢ ЭЛЕМЕНТЛИК ҚУРАМЫНА МӘДЕНИЙ ЕГИНЛЕРДИҢ ТӘСИРИ - Жумамуратов, А.; Жумамуратов, М.А.; Сыдиков, И.М. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of changes in the microelements of soil when growing the cultural plants by the method of neutron-activational analysis.
Keywords: microelement; soil; cultural plants; neutron-activational analysis; mathematical modelling